Media use and political efficacy in Malaysia: Comparing their roles in 2012 and 2013 - Idid, Syed Arabi; Sheikh Yusuf Ahmed, Ismail (2017)
Citizen participation is a central concern in a practicing democracy. What facilitates political participation have always drawn scholarly interest. Sociodemographic factors like education, political knowledge and gender, are often cited as determinants of political participation. Forms of media use and media credibility have been added to explain for political efficacy, among other forms of political behavior and political participation. Many studies on political efficacy or political participation, were mainly conducted in a one period. If changes do occur in a cross-sectional study, such a significant political development may not be discussed. This study, covering a two year period, addresses the issues of the methodology by looking at the changes in media use and the perceived media credibility to understand for changes in political efficacy. Two nationwide studies in 2012 and 2013, involving 3000 respondents, compared media use and credibility, with the dimensions of political efficacy. A factor analysis on the political efficacy items, extracted three dimensions, namely Voter Efficacy, Internal Efficacy and External Efficacy. The results of hierarchical regression suggested that traditional and new media use, as well as media credibility dimensions, were significantly correlated with political efficacy, but different levels of media use and credibility, contributed differently to the various efficacy dimensions. The results of the two studies, were compared to understand the changing political scenario of the country. We further elaborated on the implications and made several recommendations.